2008
DOI: 10.1002/jnr.21677
|View full text |Cite
|
Sign up to set email alerts
|

Selective death of newborn neurons in hippocampal dentate gyrus following moderate experimental traumatic brain injury

Abstract: Memory impairment is one of the most significant residual deficits following traumatic brain injury (TBI) and is among the most frequent complaints heard from patients and their relatives. It has been reported that the hippocampus is particularly vulnerable to TBI, which results in hippocampus-dependent cognitive impairment. There are different regions in the hippocampus, and each region is composed of different cell types, which might respond differently to TBI. However, regional and cell type-specific neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
120
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 93 publications
(138 reference statements)
16
120
0
Order By: Relevance
“…We previously reported that most of the dead cells in the HDG following moderate CCI-injury are immature neurons. 38 As the injury severity increased to the severe level, the FJB-positive cells were not only located at the inner 1/3 of the granular cell layer, they also were observed in the outer granular cell layer and hilus (Fig. 2D), where mature granular neurons and mature interneurons locate.…”
Section: Assessing Different Severities Of Tbi Induced By a CCI Modelmentioning
confidence: 89%
See 2 more Smart Citations
“…We previously reported that most of the dead cells in the HDG following moderate CCI-injury are immature neurons. 38 As the injury severity increased to the severe level, the FJB-positive cells were not only located at the inner 1/3 of the granular cell layer, they also were observed in the outer granular cell layer and hilus (Fig. 2D), where mature granular neurons and mature interneurons locate.…”
Section: Assessing Different Severities Of Tbi Induced By a CCI Modelmentioning
confidence: 89%
“…37 Moderate TBI introduced a cortical cavity (cavity volume is 14.3% -1.0%; p = 0.001; Fig. 1C, 1E) with an intact corpus callosum, 38 while severe TBI dramatically increased cavity volume to 26.2% -1.8% ( p < 0.001; Fig. 1D, 1E), further destroyed the corpus callosum, and even deformed the hippocampal structure.…”
Section: Assessing Different Severities Of Tbi Induced By a CCI Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…TAT-CBD3 Protects Neurons against Traumatic Brain InjuryTo assess if TAT-CBD3 has neuroprotective effects in vivo, we employed a CCI model of moderate TBI (36,38,39,63). Five minutes following TBI, mice received intraperitoneal injection of TAT-CBD3 or saline.…”
Section: Tat-cbd3 Reduces Cortical Nmdar-mediated Eepscs-mentioning
confidence: 99%
“…4). Neuronal death was assessed using FJB stain to label dying neurons (40) at 24 h following TBI because this time represents the peak of cell death within the hippocampus (63). Dying neurons were mainly observed in the ipsilateral neocortex around the lesion area (Fig.…”
Section: Tat-cbd3 Reduces Cortical Nmdar-mediated Eepscs-mentioning
confidence: 99%